Mental health inequalities in 9 former Soviet Union countries: Evidence from the previous decade. (January 2015) - Goryakin, Yevgeniy; Suhrcke, Marc; Roberts, Bayard; McKee, Martin
Abstract: In the previous two decades, countries of the former Soviet Union underwent substantive economic and social changes. While there has been some limited evidence on the relationship between socioeconomic well-being and mental health in the developing and transitional economies, the evidence on economic inequalities in mental health has so far been scarce. In this paper, we analyse two unique datasets collected in 2001 ( N  = 18, 428) and in 2010 ( N  = 17, 998) containing data on 9 countries of the former Soviet Union, exploring how mental health inequalities have changed between 2001 and 2010. Using regression analysis, as well as the indirect standardization approach, we found that mental health appears to have substantially improved in most studied countries during the past decade. Specifically, both the proportion of people with poor mental health, as well as wealth-related inequalities in poor mental health, decreased in almost all countries, except Georgia. Hence, we did not find evidence of a trade-off between changes in average and distributional mental health indicators between 2001 and 2010. Our findings give ground for optimism that at least on these measures, the most difficult times associated with the transition to a market economy in this region may be coming to an end. Highlights: Mental health improved in most fSU countries in 2000 decade. This was generally accompanied by decreases in inequalities in mental health. Georgia experienced the greatest increase in mental health inequalities.